Role of microRNAs in Vascular Remodeling - Fang, Y.-C.; Yeh, C.-H. (Current Molecular Medicine, 2015)
Besides being involved in the gradual formation of blood vessels during embryonic development, vascular remodeling also contributes to the progression of various cardiovascular diseases, such as; myocardial infarction, heart failure, atherosclerosis, pulmonary artery hypertension, restenosis, aneurysm, etc. The integrated mechanisms; proliferation of medial smooth muscle cell, dysregulation of intimal endothelial cell, activation of adventitial fibroblast, inflammation of macrophage, and the participation of extracellular matrix proteins are important factors in vascular remodeling. In the recent studies, microRNAs (miRs) have been shown to be expressed in all of these cell-types and play important roles in the mechanisms of vascular remodeling. Therefore, some miRs may be involved in prevention and others in the aggravation of the vascular lesions. miRs are small, endogenous, conserved, single-stranded, non-coding RNAs; which degrade target RNAs or inhibit translation post-transcriptionally. In this paper, we reviewed the function and mechanisms of miRs, which are highly expressed in various cells types, especially endothelial and smooth muscle cells, which are closely involved in the process of vascular remodeling. We also assess the functions of these miRs in the hope that they may provide new possibilities of diagnosis and treatment choices for the related diseases.
Keywords: proliferation